Waveguide lasing from V-shaped ZnO microstructure - Lee, Sang Hyun; Goto, Takenari; Miyazaki, Hiroshi; Yao, Takafumi (OPTICAL SOC AMER, 2013)
A V-shaped optical resonance cavity was obtained from ZnO microstructures grown by thermal chemical vapor deposition. Strong laser emissions were observed in three regions-the tip of the two branches and the bottom facet of the V-shaped microstructures-under UV laser excitation at room temperature. In the region where the diameter of the branches was smaller than the wavelength of the laser light, light could not propagate into the tip due to the cutoff phenomenon, resulting in partial reflection. Quasi-Fabry-Perot resonance in the branch and light reflection at the bottom facet characterized the V-shaped microcavity. (C) 2013 Optical Society of America
Keywords: ROOM-TEMPERATURE; LASER-EMISSION; NANOWIRE; ELECTROLUMINESCENCE